1997
DOI: 10.1042/bj3220529
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of sn-1-stearoyl-2-arachidonoylglycerol kinase from pig testes

Abstract: 1-Stearoyl-2-arachidonoylglycerol (SAG) kinase was identified in the particulate fraction of pig testes. This activity was enriched by hydroxyapatite and blue dye chromatography. The enzyme was selective for polyunsaturated diradylglycerol species and activity was not modulated by other diradylglycerol species or sphingomyelin metabolites. Further purification resulted in the isolation of 55 and 50 kDa proteins that corresponded with SAG kinase activity. These results support the view that the phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…We could not present direct evidence that arachidonic acid released by PLA # after stimulation with SPC does indeed derive from phosphatidic acid generated by DAG kinase. However, we showed that the levels of polyunsaturated DAG and phosphatidic acid species increased after SPC stimulation, as reported by others [25,46], and this suggests that it is the polyunsaturated DAG that is converted predominantly to phosphatidic acid by some isoforms of DAG kinase [44,47]. Since the pertussis toxin-sensitive phosphatidic acid production by SPC in CFNP9o − cells was revealed only in the presence of AACOCF $ , this suggests that arachidonic acid might be released from DAG kinase-generated phosphatidic acid, producing lysophosphatidic acid, which seems therefore to be the intracellular messenger able to release Ca# + from internal stores.…”
Section: Discussionsupporting
confidence: 88%
“…We could not present direct evidence that arachidonic acid released by PLA # after stimulation with SPC does indeed derive from phosphatidic acid generated by DAG kinase. However, we showed that the levels of polyunsaturated DAG and phosphatidic acid species increased after SPC stimulation, as reported by others [25,46], and this suggests that it is the polyunsaturated DAG that is converted predominantly to phosphatidic acid by some isoforms of DAG kinase [44,47]. Since the pertussis toxin-sensitive phosphatidic acid production by SPC in CFNP9o − cells was revealed only in the presence of AACOCF $ , this suggests that arachidonic acid might be released from DAG kinase-generated phosphatidic acid, producing lysophosphatidic acid, which seems therefore to be the intracellular messenger able to release Ca# + from internal stores.…”
Section: Discussionsupporting
confidence: 88%
“…In PAE cells there is a large amount of polyunsaturated DAG (over 25% of total DAG) [23]. In vitro studies have shown that the DGKϵ isoform is the only DGK isoform which shows specificity for a DAG containing a polyunsaturated fatty acid [25–27]. This specificity has been the subject of a very recent in vivo study confirming the selective removal of solely polyunsaturated DAG species by DGKϵ in stably DGKϵ‐transfected PAE cells [28].…”
Section: Resultsmentioning
confidence: 91%
“…Another example for highly specific interactions of soluble protein with lipid is the specific recognition of a single molecular diacylglycerol (DAG) species by a DAG-kinase in pig testes [55]. Its human homologue, DGK, was shown to be highly selective for arachidonate-containing species of DAG, providing a mechanism by which the cell can inactivate the lipid branch of the phosphoinositide-signalling pathway.…”
Section: Highly Specific Protein-lipid Interactions Of Soluble Proteinsmentioning
confidence: 99%